2018
DOI: 10.2478/jdis-2018-0021
|View full text |Cite
|
Sign up to set email alerts
|

Redesigning the Model of Book Evaluation in the Polish Performance-based Research Funding System

Abstract: Purpose This study aims to present the key systemic changes in the Polish book evaluation model to focus on the publisher list, as inspired by the Norwegian Model. Design/methodology/approach In this study we reconstruct the framework of the 2010 and 2018 models of book evaluation in Poland within the performance-based research funding system. Findings For almost 20 years the book evaluation system in Poland has been based on the verification of various technical criteria (e.g. length of the book). The new 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…In many countries, universities annually report their complete bibliographic record of peerreviewed publications to the government as part of performance-based research funding systems (PRFS) (Giménez-Toledo, Mañana-Rodríguez, et al, 2017Hicks, 2012;Sı le, Guns, et al, 2017;Sı le, Pölönen, et al, 2018). In Norway, Denmark, Finland, Flanders (Belgium), and Polandcountries that have in some form adapted the so-called Norwegian model of PRFS-the national bibliographic database either substitutes the universities' local Current Research Information Systems (CRIS) or integrates publication data from the local CRIS (Aagaard, 2018;Kulczycki & Korytkowski, 2018;Pölönen, 2018;Sivertsen, 2016aSivertsen, , 2016cSivertsen, , 2017Sivertsen, , 2018a. Comparisons with the comprehensive national publication data have shown that especially in the social sciences and humanities (SSH), WoS and Scopus coverage is seriously lacking, mainly due to the importance of national language and book publishing (Aksnes & Sivertsen, 2019;Giménez-Toledo et al, 2016Kulczycki, Engels, et al, 2018;Kulczycki, Guns, et al, 2020;Ossenblok, Engels, & Sivertsen, 2012;Sivertsen, 2016b;Sivertsen & Larsen, 2012).…”
Section: Data Sources and Methods For Oa Monitoringmentioning
confidence: 99%
“…In many countries, universities annually report their complete bibliographic record of peerreviewed publications to the government as part of performance-based research funding systems (PRFS) (Giménez-Toledo, Mañana-Rodríguez, et al, 2017Hicks, 2012;Sı le, Guns, et al, 2017;Sı le, Pölönen, et al, 2018). In Norway, Denmark, Finland, Flanders (Belgium), and Polandcountries that have in some form adapted the so-called Norwegian model of PRFS-the national bibliographic database either substitutes the universities' local Current Research Information Systems (CRIS) or integrates publication data from the local CRIS (Aagaard, 2018;Kulczycki & Korytkowski, 2018;Pölönen, 2018;Sivertsen, 2016aSivertsen, , 2016cSivertsen, , 2017Sivertsen, , 2018a. Comparisons with the comprehensive national publication data have shown that especially in the social sciences and humanities (SSH), WoS and Scopus coverage is seriously lacking, mainly due to the importance of national language and book publishing (Aksnes & Sivertsen, 2019;Giménez-Toledo et al, 2016Kulczycki, Engels, et al, 2018;Kulczycki, Guns, et al, 2020;Ossenblok, Engels, & Sivertsen, 2012;Sivertsen, 2016b;Sivertsen & Larsen, 2012).…”
Section: Data Sources and Methods For Oa Monitoringmentioning
confidence: 99%
“…In Sweden, for example, there is no PRFS, yet many Swedish universities use the Norwegian indicator and publication channel list for their internal evaluation/ assessment/funding procedures (Hammarfelt, Nelhans et al, 2016). Similarly, in Poland, a new model was introduced in 2018 that utilizes publisher lists in a scholar's habilitation procedure (Kulczycki & Korytkowski, 2018). When a candidate presents a book as his or her main achievement, it has to be from a publisher on Poland's new publisher list.…”
Section: Q13mentioning
confidence: 99%
“…Moreover, the Polish Journal Ranking has been complemented with a book publisher list established by experts and the list of conferences based on the DBLP Computer Science Bibliography and the Computing Research and Education Association of Australasia (CORE). Since 2019, the PJR and the book publisher lists are used for funding scientific institutions as well as in promotion procedures (Kulczycki, 2017;Kulczycki & Rozkosz, 2017;Kulczycki & Korytkowski, 2018).…”
Section: Research Papermentioning
confidence: 99%